The sandfish identity: phylogeographic reconstructions uncover a species complex within the Indo-Pacific distribution of Holothuria (Metriatyla) scabra - Kelly T. Brown; Paul C. Southgate; Nguyen D. Q. Duy; Lindon Havimana; Aviti J. Mmochi; Rose K. Basiita; Madjid Delghandi; Brian Stockwell; Monal M. Lal (BMC Ecology and Evolution)
Abstract Background Sea cucumbers are a highly diverse, enigmatic, ecologically and economically important group of echinoderms, however understanding of their taxonomy is complicated by cryptic morphology, hidden diversity and the presence of species complexes. The sandfish Holothuria (Metriatyla) scabra, is a high-value tropical sea cucumber exploited in multispecies fisheries across the Indo-Pacific with historically chaotic taxonomy, that has never been examined using molecular information. To evaluate its taxonomic identity, a phylogeographic approach was used to examine evolutionary relationships at 9 sites (n = 98) across the ~ 16,500 Km Indo-Pacific species distribution. Two genome-wide (1,500 PAV and 2,000 SNP) loci and one mitochondrial marker (cox1: 69 sequences) were employed in phylogenetic reconstructions, estimations of genetic distance, and assessments of species boundaries and evolutionary history. Results Both genome-wide and cox1 data indicate sandfish constitute a species complex containing a minimum of 7 operational taxonomic units (OTUs), with inter-ocean divergence patterns supporting non-conspecifity of Indian and Pacific Ocean specimens. Six OTUs were resolved in the Pacific Ocean across 3 broad lineages corresponding to putative subspecies, along with one OTU in the Indian Ocean. Analyses of evolutionary history estimate divergence of H. (Metriatyla) scabra in the early Pliocene ~ 4.36 MYa (95% HPD 3.3–5.42 MYa), from a germinate point likely in Southeast Asia within the Coral Triangle region, with subsequent diversification into the Indian and Pacific Ocean basins. Conclusions The presence of a species complex in the sandfish H. (Metriatyla) scabra is reported, providing clarity on its taxonomic identity, which prior to this study had been described exclusively on morphological characters. Given the degree of ambiguity associated with interspecific morphological descriptions of many Holothuroid taxa, data presented here describe intraspecific diversity of this valuable echinoderm.